AN EXPLORATION OF THE IMPLEMENTATION OF TECHNOLOGY-ENHANCED LANGUAGE LEARNING (TELL) THROUGH THE COMMUNITY OF INQUIRY (COI) FRAMEWORK: PRE-SERVICE ENGLISH TEACHERS’ PERSPECTIVES - Mushafiyyah, Muzayyinatul; Priajana, Nana; Ikawati, Listiana (STKIP Persada Khatulistiwa Sintang, 2025)
The integration of technology into language education has become essential, especially for pre-service English teachers who must develop innovative teaching strategies. Technology-Enhanced Language Learning (TELL) offers opportunities to foster creativity and student engagement, particularly when guided by a structured pedagogical model such as the Community of Inquiry (CoI) framework. This study explored how pre-service English teachers implemented Technology-Enhanced Language Learning (TELL) using the Community of Inquiry (CoI) framework during their teaching practicum. Using a qualitative design with interviews and teaching module analysis, the findings showed that participants applied cognitive, social, and teaching presence to create engaging learning experiences. Despite facing challenges such as limited access, low digital literacy, and difficulty sustaining CoI elements, they employed adaptive strategies such as device sharing, collaboration, and structured guidance. This study concludes that while the implementation of TELL through the CoI framework is promising, it requires ongoing support and training to address contextual constraints. The findings contribute to the development of teacher education programs and inform institutional efforts to enhance digital readiness in English language teaching.